Damaged medium model for evaluating the durability of structural steels subject to fatigue–creep mechanisms of degradation - Volkov, Ivan Аndreevich; Volkov, Аndrey Ivanovich; Korotkikh, Yuriy Georgievich; Tarasov, Ivan Sergeevich (Computational Continuum Mechanics, 2013)
Within the framework of mechanics of defective materials (MDM), a mathematical model is developed which takes into account damage accumulation in structural steels subject to combined degradation mechanisms such as fatigue and creep. A summation damage algorithm is derived to study the low cycle creep-fatigue interaction. Experimental and theoretical methods are presented to determine material parameters for MDM equations describing the degradation of the initial mechanical properties of structural materials (metals and their alloys) under fatigue and creep conditions. The process of viscoelastoplastic deformation of steel 12X18H9 is studied numerically. By comparing the obtained numerical results with the data of full scale experiments, we get the evidence supporting the validity of the constitutive MDM-relations and the methods proposed for estimating material parameters under fatigue and creep conditions.
Keywords: plasticity; creep; low- and high-cycle fatigue; mechanics of defective materials; basic experiment; damage; material parameters